2005
DOI: 10.1073/pnas.0504034102
|View full text |Cite
|
Sign up to set email alerts
|

Reduced water density at hydrophobic surfaces: Effect of dissolved gases

Abstract: Here, direct noninvasive neutron reflectivity measurements reveal the presence of a reduced (deuterated) water density region, with a sigmoidal density profile at the hydrophobic silane-water interface that depends on the type and concentration of dissolved gases in the water. Removal of dissolved gases decreases the width of the reduced water density region, and their reintroduction leads to its increase. When compared with recent computer simulations, a locally fluctuating density profile is proposed, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
270
4
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(297 citation statements)
references
References 45 publications
21
270
4
2
Order By: Relevance
“…I illu q z ðzÞ is the vertical intensity profile of the incident illumination, which depends on the incident angle α i and on the electronic structure of the monolayer. For a monolayer at the air/water interface, this electronic structure can be obtained by GIXOS and parameterized using slab models § , where each slab represents a layer of constant electron density within the monolayer (28)(29)(30). Accordingly, once the illumination profiles I illu q z ðzÞ are known, the ion concentration profiles c j ðzÞ can be reconstructed from the measured fluorescence intensities I fluo j ðq z Þ using Eq.…”
Section: Methodsmentioning
confidence: 99%
“…I illu q z ðzÞ is the vertical intensity profile of the incident illumination, which depends on the incident angle α i and on the electronic structure of the monolayer. For a monolayer at the air/water interface, this electronic structure can be obtained by GIXOS and parameterized using slab models § , where each slab represents a layer of constant electron density within the monolayer (28)(29)(30). Accordingly, once the illumination profiles I illu q z ðzÞ are known, the ion concentration profiles c j ðzÞ can be reconstructed from the measured fluorescence intensities I fluo j ðq z Þ using Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Early neutron reflectivity studies [31][32][33] of hydrocarbon-water interfaces reported gap widths larger than 10Å, while later x-ray reflectivity measurements on similar systems reported gap widths of less than 5Å. 35, 36 Yet other X-ray 30 and neutron 34 studies reported that there is no gap.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, although the water-hydrophobic interface has been studied by a number of groups, [30][31][32][33][34][35][36][37] the results are inconsistent and have not led to a consensus. Early neutron reflectivity studies [31][32][33] of hydrocarbon-water interfaces reported gap widths larger than 10Å, while later x-ray reflectivity measurements on similar systems reported gap widths of less than 5Å.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] On the other hand, incompatibility between a liquid and an adjacent solid-water against a hydrophobic surface, say-can lead to a depletion in the density of the fluid phase at the interface. [5][6][7][8][9][10][11][12][13] These deviations from bulk properties can exacerbate the chemical inhomogeneities of interfaces, altering for example the dielectric or solvation characteristics there. [14] Furthermore, ions may be depleted or enriched at the solidwater or air-water interfaces relative to the bulk, [15][16][17][18][19][20][21] an effect that involves subtle balances of enthalpic and entropic factors.…”
Section: Introductionmentioning
confidence: 99%